Salafi-Jihadist Movements and Ideology in Educational Institutions: Exploring the Nexus with Religious Moderation - Hatim Gazali; Dewi Anggraeni; Mariam Eit Ahmed (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
The global proliferation of Salafi-Jihadist movements has raised serious concerns about  ideological infiltration into educational institutions, particularly in predominantly Muslim  countries like Indonesia. This study aims to explore how Salafi-Jihadist ideology manifests  within Islamic educational institutions and how such influence interacts with state-promoted  religious moderation programs. Positioned within a critical historical framework, this research  employs a qualitative design that integrates content analysis of scholarly literature and actor based inquiry to map the ideological characteristics of Salafi-Jihadism and the institutional  responses to its spread. The findings highlight three key insights: first, Salafi-Jihadist  movements present a doctrinally rigid and exclusionary interpretation of Islam that challenges  inclusive religious practices; second, the ideological appeal of Salafi-Jihadism lies in its claim  to scriptural authenticity and puritanical simplicity, making it attractive to specific youth  cohorts; and third, religious moderation initiatives—particularly through curriculum reform,  institutional policy, and cultural engagement—serve as effective counter-strategies to mitigate  radical influences. These findings offer important implications for policymakers, educators,  and religious leaders, emphasizing the urgency of developing preventive frameworks that  integrate theological inclusivity and critical pedagogy. Ultimately, the study contributes to a  deeper understanding of the ideological contestations within Islamic education and proposes  grounded strategies to safeguard religious institutions from extremism